Migrant labor & the moral imperative Filipino workers in Qatar and the United Arab Emirates in the 21st century - Dolaman, Waverly (Ann Arbor Michigan ProQuest LLC, 2011)
Migrant work is a critical part of the Philippines' economy. In 2009, remittances, or money sent back to the Philippines from citizens working abroad, comprised 10 percent of the country's gross domestic product (GDP). But these earnings often come at a heavy price, as migrant laborers encounter a host of abusive practices at the hands of Filipino recruitment agencies and Middle Eastern employers. The aim of this thesis is threefold. First, it provides information on and exposes this human rights issue, convincing readers of the "moral imperative" to help stop these abuses. Second, it explores the need for migrant workers, and the vulnerability of Filipino workers who do not have adequate work opportunities in the Philippines. Third, it offers solutions to improve working conditions for Filipino workers in Qatar and the United Arab Emirates (UAE). Although the thesis begins with a historical introduction, the scope of the work is the first decade of the twenty-first century, while the countries examined are the Philippines, Qatar and the UAE. The thesis is organized into five parts. Chapter One: "Introduction: A Brief Overview of Philippine History" sets the stage by providing necessary background information on the Philippines. Chapter Two: "The Demand by Qatar and the UAE for Migrant Workers" discusses the need for overseas Filipino workers (OFWs) in these two countries and outlines important definitions and statistics. Chapter Three: "The Plight of Filipino Workers in Qatar and the UAE" then deals with five aspects of their plight: desperate need for a job, expensive journey to the Middle East, dangerous work conditions, problems with remuneration and substandard living conditions. Chapter Four: "Shared Responsibility: The Role of the Philippines, Qatar and UAE Governments and Other Interested Parties in the Filipino Migrant Worker Problem" investigates how each government fails to adequately protect OFWs, and analyzes the efforts of interested parties, such as the United Nations (UN) and Human Rights Watch, in helping migrant workers. Chapter Five: "Conclusion: Recommendations to Address the OFW Problem" proposes solutions to improve the Filipino migrant labor situation, such as creating jobs within the Philippines and drawing more attention to human rights abuses, especially by governments and employers. The final chapter compares and contrasts the plight of Filipino workers in both Middle Eastern countries and notes that more needs to be done to alleviate this problem.--Abstract.
Thesis (M.A.L.S.)--Georgetown University, 2010.
Keywords: Migrant labor; Employment